ANEMIA PREVENTION IN PREGNANT WOMEN - Aditya Nugraha; Sukmawati Sukmawati; Yusshy Kurnia Herliani (Journal of Maternity Care and Reproductive Health, 2020)
The number of anemia cases in pregnant women is still high, various precautions have been taken. This study aims to determine anemia prevention actions in pregnant women. The study design used a quantitative descriptive approach. The samples in this study were 84 pregnant women selected using accidental sampling techniques. The research instrument used a questionnaire developed by researchers with a validity test value of 0.679-0.979 and a reliability test with a value of Cronbach alpha 0.965. Univariate data analysis. The results of the study showed that almost all pregnant women had received health education, the majority of pregnant women consumed Fe tablets properly and correctly, consumed a balanced diet, practicing a healthy lifestyle, and almost all routinely performed ANC. Conclusion, anemia prevention efforts in pregnant women are mostly done, listening to health education, conducting ANC and doing a healthy life. It is expected that the health professional would work together and the family would supervise pregnant women in consuming Fe tablets according to the rules and intensively provide counseling about a balanced diet.Keywords: Anemia, pregnant women, prevention.